Spectrally selective fluorescence imaging of Chlorobaculum tepidum reaction centers conjugated to chelator-modified silver nanowires - Kowalska, Dorota; Szalkowski, Marcin; Ashraf, Khuram; Grzelak, Justyna; Lokstein, Heiko; Niedziolka-Jonsson, Joanna; Cogdell, Richard; Mackowski, Sebastian (Photosynthesis research, 2018)
A polyhistidine tag (His-tag) present on Chlorobaculum tepidum reaction centers (RCs) was used to immobilize photosynthetic complexes on a silver nanowire (AgNW) modified with nickel-chelating nitrilo-triacetic acid (Ni-NTA). The optical properties of conjugated nanostructures were studied using wide-field and confocal fluorescence microscopy. Plasmonic enhancement of RCs conjugated to AgNWs was observed as their fluorescence intensity dependence on the excitation wavelength does not follow the excitation spectrum of RC complexes in solution. The strongest effect of plasmonic interactions on the emission intensity of RCs coincides with the absorption spectrum of AgNWs and is observed for excitation into the carotenoid absorption. From the absence of fluorescence decay shortening, we attribute the emission enhancement to increase of absorption in RC complexes.
Keywords: Conjugation; roztoky; Nanowires; Fluorescence; Silver nanowires; Chelating Agents; fotosyntetická reakční centra (proteinové komplexy); nanodráty; Bacteriochlorophyll; Chlorobi; Silver; chelátory; Solutions; Spectrometry, Fluorescence; stříbro; Plasmonic enhancement; fluorescenční spektrometrie; Photosynthetic Reaction Center Complex Proteins